Badass : a relentless onslaught of the toughest warlords, vikings, samurai, pirates, gunfighters, and military commanders to ever live /: a relentless onslaught of the toughest warlords, vikings, samurai, pirates, gunfighters, and military commanders to ever live. (2009) - Unknown
No abstract available